2004
DOI: 10.1111/j.1365-2591.2004.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to localized corrosion of stainless steel and NiTi endodontic instruments in irrigating solutions

Abstract: None of the tested materials is susceptible to pitting or crevice corrosion in R-EDTA and NaOCl solutions and from this standpoint are appropriate for the production of endodontic files.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 24 publications
7
57
0
3
Order By: Relevance
“…Endodontic file instruments are designed to be used at body temperature, which is 37° C approximately [29]. Endodontic files were heat up to body temperature with a a Bosch hot air 12 gun D-70745, since room temperature was at ~20° C at the time the experiment was run.…”
Section: Experimental Validation Of the Numerical Resultsmentioning
confidence: 99%
“…Endodontic file instruments are designed to be used at body temperature, which is 37° C approximately [29]. Endodontic files were heat up to body temperature with a a Bosch hot air 12 gun D-70745, since room temperature was at ~20° C at the time the experiment was run.…”
Section: Experimental Validation Of the Numerical Resultsmentioning
confidence: 99%
“…Significant signs of surface corrosion were reported by O' Hoy and colleagues 20) after overnight immersion, whereas Darabara et al 21) found no signs of corrosion after immersion for 1 hour in 5.25% NaOCl and 17% ethylenediaminetetraacetic acid (EDTA) heated to 37℃. The inconsistent results are due mainly to the different study conditions and interpretations.…”
Section: ⅰ Introductionmentioning
confidence: 91%
“…Apart from reasons mentioned for the fatigue failure of NiTi instruments, others have suggested that the corrosion mechanisms, as a result of chemomechanical preparation and chemical disinfection or sterilisation, might be an initial factor for fatigue failure. These authors have questioned the effect of pitting or crevice corrosion on the surface of endodontic NiTi rotary instruments (12,13).…”
Section: Highlightsmentioning
confidence: 99%